2012
DOI: 10.1108/02635571211225512
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of suppliers' level of use of B2B e‐marketplaces

Abstract: Purpose -The purpose of this paper is to investigate the influence of various factors on suppliers' level of use of business-to-business (B2B) e-marketplaces by examining three basic variable domains; suppliers' internal environment, their external environment and the characteristics of the adopted B2B e-marketplace. Design/methodology/approach -A conceptual framework is developed based on extended literature review and examined on data collected from 87 suppliers that currently use Greek B2B e-marketplaces. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
1
15
2
Order By: Relevance
“…Several previous studies [1,16,37] proposed that the adoption of e-business tools is not uniform across all regions and countries; however this study indicates that there is some amount of uniformity with regard to these particular tools.…”
Section: A Usage Of E-business Toolscontrasting
confidence: 54%
See 1 more Smart Citation
“…Several previous studies [1,16,37] proposed that the adoption of e-business tools is not uniform across all regions and countries; however this study indicates that there is some amount of uniformity with regard to these particular tools.…”
Section: A Usage Of E-business Toolscontrasting
confidence: 54%
“…As a result, there have been numerous studies investigating the drivers that encourage organizations to adopt these tools; some such drivers include the availability of in-house skills and knowledge [15] as well as organizational and financial readiness, and pressure from competitors and supply chain partners [16]. Upon reviewing the literature, the authors of this study identified 10 drivers of e-business tool adoption, with these being categorized as either internal or external.…”
Section: B Drivers For Adopting E-business Toolsmentioning
confidence: 99%
“…An extensive literature review that concerned the Business-To Business relationships journal articles that were published between 2009 and 2012 was presented by Meixner et al (2009), Canavari et al (2010 and by Saprikis and Vlachopoulou (2012). However, a multicriteria analysis on evaluating the performance of Greek agricultural enterprises has been applied by Baourakis et al (2002) and by Kalogeras et al (2005).…”
Section: E-marketingmentioning
confidence: 99%
“…An extensive literature review that concerned the Business-To Business relationships journal articles that were published between 2009 and 2012 was presented by Meixner et al (2009), Canavari et al (2010 and by Saprikis and Vlachopoulou (2012). However, a multicriteria analysis on evaluating the performance of Greek agricultural enterprises has been applied by Baourakis et al (2002) and by Kalogeras et al (2005).…”
Section: E-marketingmentioning
confidence: 99%